Lepidium s. str. (Brassicaceae) in the flora of Ukraine - Ilyinska, Antonina P. (Biodiversity: Research and Conservation, 2015)
The key to the 14 species of Lepidium occurring in the Ukraine, including basionyms and the most important synonyms, and distribution of these species within the floristic regions, especially in Ukraine, are presented